Physicochemical and sensory characteristics of milk from cows in different lactation stages and calving orders - Barreto, Mayara Leilane de Jesus (2016)
Knowledge of the variation in milk composition is essential for determining milk quality, which is defined by several organoleptic properties. This study evaluated the effect of lactation stage and calving order on the physicochemical composition and sensory characteristics of milk from primiparous and multiparous lactating dairy cows. Milk samples were collected monthly from December 2011 to May 2012. Data were analyzed using ANOVA followed by Tukey’s test (p < 0.05). Milk production (PROD), somatic cell count (SCC), and milk urea nitrogen (MUN) were significantly higher in multiparous cows, whereas the casein to total protein ratio (C/TP) was significantly higher in primiparous cows. All milk components except for non-fat dry solids (NDE) were significantly affected by lactation stage. Body condition score (BCS) was not affected by calving order or lactation stage. Color was the only sensory attribute affected by calving order. In conclusion, the physicochemical properties and sensory attributes of milk were affected by calving order and lactation stage.